Impact of Hospitalization and Medication Switching on Post‐discharge Adherence to Oral Anticoagulants in Patients With Atrial Fibrillation. Issue 10 (21st September 2020) - Pham Nguyen, Thanh Phuong; Chen, Yong; Thibault, Dylan; Leonard, Charles E.; Hennessy, Sean; Willis, Allison
Abstract : Background : Adherence to chronic medications remains poor in practice. There is limited evidence on how hospitalization affects post‐discharge adherence to oral anticoagulants (OACs) in individuals with atrial fibrillation. The aim of this study was to examine the impact of hospitalization and medication switching on post‐discharge adherence to OACs in the population with atrial fibrillation. Methods : A quasi‐experimental pre–post observational study was conducted using United States commercial insurance health care claims from the 2009 to 2016 Optum database. Adults with atrial fibrillation taking OACs who had a random hospitalization occurring after the first observed OAC prescription fill and no other admission in the preceding and following 6 months were identified. OAC adherence was estimated by the proportion of days covered within 6 and 12 months before and after hospitalization. Difference‐in‐difference analysis was employed to compare the pre‐hospitalization and post‐hospitalization proportion of days covered, stratified by reasons for hospitalization (i.e., bleeding vs non–bleeding‐related reasons) and adjusting for imbalanced baseline characteristics between groups. Change in adherence when the OAC was switched at discharge was also examined. Results : The 22, 429 individuals who met study criteria were predominantly male (52.4%), white (77.2%), and older age (median 74 years). A clinically significant hemorrhage was the reason for 1029 (4.5%) of qualifying hospitalizations. After covariate adjustment, there was a reduction in the proportion of days covered after discharge, regardless of admission diagnosis (p<0.0001). The 6‐month difference‐in‐difference analyses revealed that adherence was incrementally reduced by 3.2% (p=0.0003) in the bleeding group compared with the nonbleeding group, whereas switching from warfarin to a direct oral anticoagulant after hospitalization was associated with a smaller reduction by 3.4% in adherence (p=0.0342) compared with other switchers, regardless of the reason for hospitalization. The 12‐month difference‐in‐difference analyses revealed similar results. Conclusions : Hospitalization is temporally associated with a reduction in adherence to OACs, regardless of reason for hospitalization. More effective strategies are needed to improve OAC adherence, particularly during transition of care